Perceptions of local population on the impacts of substitution of fossil energies by renewables: A case study applied to a Spanish rural area - P. Gargallo; N. García-Casarejos; Manuel Salvador (Energy Reports, 2020)
Using the perceptions of a sample of 231 people from a Spanish region as a case study, this paper aims to respond to the increasing demand for measurement of economic, social and environmental performance of renewables implementation. First, from this information, the paper analyzes the willingness to pay of the rural community for the complete replacement of fossil fuels with clean ones throughout the region. Second, it explores this rural community's perceptions in order to determine the most outstanding outputs, outcomes and impacts for the whole renewable energy penetration.
Keywords: 330; Impact; Outcome; Output; Perception; Renewable; Willingness to pay